Pharmacokinetics of Melagatran and the Effect on Ex Vivo Coagulation Time in Orthopaedic Surgery Patients Receiving Subcutaneous Melagatran and Oral Ximelagatran: A Population Model Analysis - Eriksson, Ulf G; Mandema, Jaap W; Karlsson, Mats O; Frison, Lars; Olsson Gisleskog, Per; W??hlby, Ulrika; Hamr??n, Bengt; Gustafsson, David; Eriksson, Bengt I (Clinical pharmacokinetics, 2003)
Ximelagatran, an oral direct thrombin inhibitor, is rapidly bioconverted to melagatran, its active form. The objective of this population analysis was to characterise the pharmacokinetics of melagatran and its effect on activated partial thromboplastin time (APTT), an ex vivo measure of coagulation time, in orthopaedic surgery patients sequentially receiving subcutaneous melagatran and oral ximelagatran as prophylaxis for venous thromboembolism. To support the design of a pivotal dose-finding study, the impact of individualised dosage based on bodyweight and calculated creatinine clearance was examined. Pooled data obtained in three small dose-guiding studies were analysed. The patients received twice-daily administration, with either subcutaneous melagatran alone or a sequential regimen of subcutaneous melagatran followed by oral ximelagatran, for 8-11 days starting just before initiation of surgery. Nonlinear mixed-effects modelling was used to evaluate rich data of melagatran pharmacokinetics (3326 observations) and the pharmacodynamic effect on APTT (2319 observations) in samples from 216 patients collected in the three dose-guiding trials. The pharmacokinetic and pharmacodynamic models were validated using sparse data collected in a subgroup of 319 patients enrolled in the pivotal dose-finding trial. The impact of individualised dosage on pharmacokinetic and pharmacodynamic variability was evaluated by simulations of the pharmacokinetic-pharmacodynamic model. The pharmacokinetics of melagatran were well described by a one-compartment model with first-order absorption after both subcutaneous melagatran and oral ximelagatran. Melagatran clearance was correlated with renal function, assessed as calculated creatinine clearance. The median population clearance (creatinine clearance 70 mL/min) was 5.3 and 22.9 L/h for the subcutaneous and oral formulations, respectively. The bioavailability of melagatran after oral ximelagatran relative to subcutaneous melagatran was 23%. The volume of distribution was influenced by bodyweight. For a patient with a bodyweight of 75kg, the median population estimates were 15.5 and 159L for the subcutaneous and oral formulations, respectively. The relationship between APTT and melagatran plasma concentration was well described by a power function, with a steeper slope during and early after surgery but no influence by any covariates. Simulations demonstrated that individualised dosage based on creatinine clearance or bodyweight had no clinically relevant impact on the variability in melagatran pharmacokinetics or on the effect on APTT. The relatively low impact of individualised dosage on the pharmacokinetic and pharmacodynamic variability of melagatran supported the use of a fixed-dose regimen in the studied population of orthopaedic surgery patients, including those with mild to moderate renal impairment.